Helicobacter pylori resistome analysis in Colombia - Guzmán-Bastidas, Kevin Andres; López-Daza, Sophia Fernanda (Universidad y Salud, 2026)
Introduction: Helicobacter pylori is a bacterium closely associated with chronic gastritis and gastric cancer. In Colombia, its high prevalence, along with marked geographical differences in gastric cancer incidence, has prompted studies focused on the antimicrobial resistance of this bacterium. Objective: To characterize the resistome of Helicobacter pylori in Colombia through the analysis of phenotypic and genotypic studies, in order to evaluate resistance pa erns. Materials and Methods: A systematic review was conducted in scientific databases, selecting 21 original studies. Mutations in resistance-associated genes were evaluated, and a descriptive statistical analysis was performed using R software. Results: High resistance to metronidazole was identified, along with variable resistance to clarithromycin and tetracycline, moderate resistance to amoxicillin and levofloxacin, and low resistance to furazolidone and rifampicin. Conclusion: The high resistance to metronidazole excludes it as a reliable first-line option. The variable resistance to clarithromycin and tetracycline requires regional susceptibility testing. Amoxicillin and levofloxacin retain moderate efficacy, while furazolidone and rifampicin stand out as promising alternatives. It is essential to implement phenotypic or genotypic susceptibility testing prior to treatment and to update empirical guidelines based on local resistance surveillance.